PRE-SCHOOL EDUCATION CHARACTERISTICS AND FUNCTIONAL PURPOSE - Abduramanova Diana Valeryevna, Abduramanova Diana Valeryevna (Журнал иностранных языков и лингвистики, 2021)
The emergence and development of pedagogy as a science is associated with the practical need of society to study and generalize the historical experience of preparing new generations to participate in the production of material and spiritual values. Modern pedagogy is a special area of the science of human education at all age stages of its development. Each science has its own subject, i.e. she studies a certain area of reality. For pedagogy, such an area of reality is education. She studies the essence of upbringing, its deep internal mechanisms, the relationship with the development of the personality and the external conditions of its existence. Therefore, the most basic concept of pedagogy is education, all other concepts concretize and expand it.